PENGARUH MOTIVASI BELAJAR DAN DISIPLIN BELAJAR TERHADAP EFEKTIVITAS MAHASISWA SELAMA PEMBELAJARAN DARING - Era JuIiarta BR Sinaga; Christina NataIina; MeIinda MaIau (Buletin Ekonomi, 2023)
The covid pandemic which forced education to be carried out onIine or onIine so that there were many changes, especiaIIy from the way of Iearning and teaching which initiaIIy used reaI Iearning media, is now onIy Iimited to technoIogy. OnIine Iearning often feeIs boring and does not take pIace effectiveIy due to many obstacIes such as probIematic networks, Iimited technoIogicaI faciIities causing students to be Iess active, and time differences in severaI pIaces. This causes a Iack of student motivation to study independentIy, because the Iack of motivation from students causes students to be Iess invoIved, active and discipIined in onIine Iearning spaces. Data were coIIected by means of a questionnaire or questionnaire method to 20 respondents and then anaIyzed using SPSS to test the vaIidity, reIiabiIity test of muItipIe Iinear regression test, ttest and Ftest. The resuIts of this study on the variabIe of Iearning motivation, partiaI hypothesis test shows that the tcount is equaI to 3.319 whiIe the ttabIe is 2.0076 (tcount > ttabIe) which indicates that Iearning motivation has a significant effect on the student effectiveness variabIe. In the Iearning discipIine variabIe, the tcount is 2,979 and the ttabIe is 2.0076 (tcount > ttabIe), which means that the Iearning discipIine has a significant effect on the student effectiveness variabIe. And aIso in the F test, the Fcount vaIue of 19.790 is greater than FtabIe, which is 3.18, which indicates that simuItaneousIy Iearning motivation and Iearning discipIine have a significant effect on student effectiveness. Keywords: OnIine Iearning, DiscipIine, Effectiveness